Vps10p Transport from the trans-Golgi Network to the Endosome Is Mediated by Clathrin-coated Vesicles - Deloche, Olivier (The American Society for Cell Biology, 2001)
A native immunoisolation procedure has been used to investigate the role of clathrin-coated vesicles (CCVs) in the transport of vacuolar proteins between the trans-Golgi network (TGN) and the prevacuolar/endosome compartments in the yeast Saccharomyces cerevisiae. We find that Apl2p, one large subunit of the adaptor protein-1 complex, and Vps10p, the carboxypeptidase Y vacuolar protein receptor, are associated with clathrin molecules. Vps10p packaging in CCVs is reduced in pep12Δ and vps34Δ, two mutants that block Vps10p transport from the TGN to the endosome. However, Vps10p sorting is independent of Apl2p. Interestingly, a Vps10C(t)Δp mutant lacking its C-terminal cytoplasmic domain, the portion of the receptor responsible for carboxypeptidase Y sorting, is also coimmunoprecipitated with clathrin. Our results suggest that CCVs mediate Vps10p transport from the TGN to the endosome independent of direct interactions between Vps10p and clathrin coats. The Vps10p C-terminal domain appears to play a principal role in retrieval of Vps10p from the prevacuolar compartment rather than in sorting from the TGN.